Green Credit, Climate Risk, and Credit Risk in the Indonesian Banking Industry - Warninda, Titi Dewi; Widodo, Shelby Devianty (UI Scholars Hub, 2026)
As the largest archipelagic country, Indonesia's industries and regions are particularly vulnerable to the impacts of climate change. This research examines the effects of green credit policy and climate risk, specifically sea level rise and precipitation, on bank credit risk. Using data from 2019 to 2023 and system GMM, the research results show that the higher the sea level rise and precipitation, the higher the credit risk. The findings of this research also indicate that a higher proportion of green credit lowers bank credit risk, and bank inefficiency strengthens the impact of green credit on credit risk. The results of this research underscore the need to consider climate risk and the impact of green credit on reducing bank credit risk. The results also suggest that banks should enhance their effectiveness in assessing and monitoring loan portfolios.